The impact of the COVID-19 pandemic on people living with HIV in Zimbabwe. Issue 2 (3rd April 2022) - Madzima, Bernard; Makoni, Tatenda; Mugurungi, Owen; Mudariki, Godfrey; Mpofu, Amon; Dube, Freeman; Munangaidzwa, Lameck; Taramusi, Isaac
Abstract : The COVID-19 pandemic was reported from March 2020 in Zimbabwe. COVID-19 containment measures which included repeated lockdowns have disrupted community interactions, reduced working hours, restricted travel and restricted HIV services for people living with HIV (PLHIV), among others. The study adopted a cross-sectional design. Both qualitative and quantitative data were collected in all the 10 provinces and analysed. A sample size of 480 was calculated for the cross-sectional survey. Secondary data on HIV early warning indicators from 2018 to 2021 were extracted from 20 randomly selected health facilities and used for modelling. Mathematical modelling was conducted to assess the impact of COVID-19 on PLHIV. AIDS-related deaths increased from 20 100 in 2019 to 22 200 in 2020. In addition, there were significant years of life lost (yLLs) from premature mortality and years of life lost due to disability (yLDs) from COVID-19. Prevalence of COVID-19 among PLHIV was 4%. COVID-19 vaccination coverage was 64%, which is higher than the national average of 42%. Stress and breach of confidentiality as ARV medicines were given out in open spaces and fear of contracting COVID-19 were the perceived psychological issues. COVID-19 disrupted HIV service provision, increased AIDS-related deaths and caused psychological challenges.